Allocation and Distribution in Islamic Economics the Role of Islamic Monetary and Fiscal Policy in Realizing Economic Justice - Ahmad Ridwansah, Asep; Al-Hakim, Sofian; Janwari , Yadi (Zona Law And Public Administration Indonesia, 2026)
This study aims to analyze the role of Islamic monetary and fiscal policy in optimizing resource allocation and wealth distribution to realize economic justice within the Islamic economic system. The method used is a literature study with a qualitative approach and descriptive analysis of Islamic monetary instruments (such as Shariah-compliant fiat money, sukuk, and profit-sharing-based financing) as well as Islamic fiscal instruments (primarily zakat, infaq, sadaqah, waqf, and sharia-compliant taxes). The results indicate that integrated Islamic monetary and fiscal policies can reduce economic disparities through productive allocation mechanisms and equitable distribution, in accordance with maqashid shariah. Further discussion outlines the implementation challenges and development opportunities for such policies in Indonesia. The implication of this research is the importance of synergy between monetary and fiscal authorities in designing policies that are not only stable, but also inclusive and equitable.